2001
DOI: 10.1097/00003246-200106000-00027
|View full text |Cite
|
Sign up to set email alerts
|

ONO-1714, a new inducible nitric oxide synthase inhibitor, attenuates diaphragmatic dysfunction associated with cerulein-induced pancreatitis in rats

Abstract: Cerulein-induced diaphragmatic dysfunction was attributable, in part, to nitric oxide overproduced via inducible nitric oxide synthase. Pretreatment with ONO-1714 at a dose of 0.1 mg/kg attenuated diaphragmatic dysfunction associated with cerulein-induced pancreatitis in rats assessed by contractile profiles and endurance capacity. This beneficial effect of ONO-1714 may be attributable, in part, to inhibition of diaphragmatic lipid peroxidation induced by nitric oxide-derived free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…Also, our observations confirmed that overproduction of NO arising from the iNOS was associated with the development of acute pancreatitis as shown by marked hyperamylasemia, increased pancreas water content, and histologically extensive acinar cell vacuolization. Our data confirm previous observations of enhanced iNOS expression and increased NO metabolites during acute pancreatitis (7,21,24,29,30). Because the amount of NO produced by cNOS is too small to be reflected in the changes of NO levels, the induction of iNOS, presumably in macrophages and vascular smooth cells, may be responsible for the large release of NO in acute pancreatitis (7).…”
Section: Discussionsupporting
confidence: 89%
“…Also, our observations confirmed that overproduction of NO arising from the iNOS was associated with the development of acute pancreatitis as shown by marked hyperamylasemia, increased pancreas water content, and histologically extensive acinar cell vacuolization. Our data confirm previous observations of enhanced iNOS expression and increased NO metabolites during acute pancreatitis (7,21,24,29,30). Because the amount of NO produced by cNOS is too small to be reflected in the changes of NO levels, the induction of iNOS, presumably in macrophages and vascular smooth cells, may be responsible for the large release of NO in acute pancreatitis (7).…”
Section: Discussionsupporting
confidence: 89%
“…[20,21,22] In the present study co-treatment of animals with raxofelast, an inhibitor of lipid peroxidation, reduced the levels of MAL, prevented the depletion of pancreatic GSH and markedly attenuated the severity of pancreatitis. As a matter of fact, raxofelast caused a reduction in the biochemical signs of pancreatitis, such as the increased serum amylase and lipase activity, improved the histological picture and decreased tissue edema.…”
Section: Discussionsupporting
confidence: 51%
“…Our hypothesis that an overproduction of NO by ecNOS and/or iNOS plays a key role in the proposed pathophysiologic sequelae of acute pancreatitis is further supported by numerous studies demonstrating beneficial effects of nonselective NOS inhibitors in acute pancreatitis [149][150][151][152] as well as after pancreatic cold [153] and warm ischemia-reperfusion [154]. These beneficial effects include the prevention of progressive and severe hypotension [150], the reduction in multiorgan oxidative stress [149] and bacterial translocation [152], as well as the attenuation of diaphragmatic dysfunction [151] in acute experimental pancreatitis.…”
Section: Potential Candidates Mediating Vasoconstriction/vasodilationmentioning
confidence: 74%
“…These beneficial effects include the prevention of progressive and severe hypotension [150], the reduction in multiorgan oxidative stress [149] and bacterial translocation [152], as well as the attenuation of diaphragmatic dysfunction [151] in acute experimental pancreatitis.…”
Section: Potential Candidates Mediating Vasoconstriction/vasodilationmentioning
confidence: 99%